The intellectual structure of game research - Martin, Paul (Game Studies Foundation, 2018)
This article maps out the main areas of game research through an analysis of co-citation and keyword co-occurrence patterns in 24,128 game research documents between 1966 and 2016. The keyword analysis identifies 4 communities: Education/Culture, Technology, Effects and Medical. Co-citation analysis identifies 5 communities: Education, Humanities/Social Science, Computer Science, Communications, and Health. Burst analysis of keywords reveals when key research themes emerged across the period. Key findings are: the main division in game research is between Communications and Health on the one hand and Education, Humanities/Social Science and Computer Science on the other; design is an important bridge between different communities; and there exists a gap in research on the game industry. The research is a broad overview and future research that targets specific communities to tease out more specific patterns is recommended, as is research targeting non-English language sources.